Tailoring Scaffolds for Orthopedic Application With Anti-Microbial Properties: Current Scenario and Future Prospects - Preethi, A.; Bellare, Jayesh R. (Frontiers in Materials, 2021)
Research in the orthopedic application has attracted the scientific community to design and develop advanced, engineered synthetic scaffolds that possess all the essential cues properties necessary for successful regeneration and restoration of tissue function. Despite having the best surgical practices, nosocomial infections like surgical site infections can negatively impact the outcome of the scaffolds that are intended only for regenerative purposes. Therefore, there is a need to include anti-microbial properties as one of the parameters while designing a scaffold. There are various methods implemented to tackle microbial colonization such as modifying the scaffold surface that deflects microbes from surface adhesion and modifying the scaffold surface by inactivating microbes upon contact while maintaining the biocompatibility of the scaffold and also maintaining the scaffold viable for new bone formation. This review lists various anti-microbial polymers and compounds available in nature and methods to incorporate them into the scaffold with polymer and ceramics as the base material, without compromising bioactivity. We have reviewed various anti-microbial compounds, biomaterials and have also identified various biomolecules (vitamins, phytochemicals and anti-microbial peptides) that can be utilized for orthopedic application.